The use of plasma exchange with albumin replacement in the management of Alzheimer’s disease: a scoping review - Cantero-Fortiz, Yahveth; Boada, Mercè (Frontiers in Neurology, 2024)
Introduction AD is a progressive neurodegenerative disorder causing significant cognitive decline and impaired daily functioning. Current treatments offer only modest relief, and many amyloid-targeting therapies have failed, prompting exploration of alternative approaches such as PE with albumin replacement. Objectives This scoping review systematically maps the literature on PE with albumin replacement in AD management, focusing on outcomes, methodologies, and reported benefits and risks. Methods A comprehensive search in PubMed, supplemented by reference scanning and hand-searching, identified studies involving PE with albumin replacement in AD patients. Data charting and critical appraisal were conducted using standardized tools. Results Seven primary studies from the AMBAR (Alzheimer Management by Albumin Replacement) trial met the inclusion criteria, consistently reporting improvements in cognitive function, positive neuroimaging results, and favorable neuropsychiatric outcomes. For instance, one study found a significant slowing of cognitive decline (p < 0.05) among patients receiving PE with albumin replacement. Another study showed better preservation of hippocampal volume and improved brain perfusion metrics in the treatment group (p < 0.05). The intervention was generally well-tolerated with manageable side effects. Conclusion PE with albumin replacement is a promising therapeutic approach for AD, warranting further investigation to confirm its efficacy and safety across broader settings. Scoping review registration https://osf.io/v6dez/?view_only=1cd9637e7e0347d39713bf19aac0dfe8.